Corporate philanthropy (Henry Stewart Talks, 2025)
Corporate philanthropy in CSR, Charity vs. philanthropy, Reasons for corporate giving, Philanthropy in business strategy, Outcome measurement and communication, Greenwashing and regulations, Transparency, engagement, and impact